PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PADA PERUSAHAAN TERDAFTAR DALAM PEMERINGKATANCGPI Tahun 2016) - Hidayatul Arohmah (Jurnal Akuntansi Indonesia, 2019)
Abstract:This research aims to analyze and obtain empirical evidence about the effects of good corporate governance and leverage on tax avoidance. The independent variables used are good corporate governance and leverage. The dependent variable used is tax avoidance. The research population was companies listed in corporate governance perception index rank during 2016 years Sample was collected by purposive sampling method. Total 26 companies were taken as study’s sample. The analysis method of this research used regression. The results of this research showed that good corporate governance which is proxied by the CGPI score (corporate governance index perception) has an effect on tax avoidance which is proxied by the effective tax rate (ETR). The results of this research also showed that tax avoidance activities are influenced by leverage. Limitations of this research are used companies listed in corporate governance perception index during 2016 as the object of research so that the conclusions of this research can’t be drawn of each industries sector because each industrial sector and company has different policies. Keywords: Good corporate governance, Corporate governance perception index, leverage, tax avoidance